Narrative episodic future thinking reduces delay discounting and enhances goal salience in the general population: an online feasibility study - Chantelle Boucher; Timothy Skinner; Carina K. Y. Chan (Health Psychology and Behavioral Medicine)
Background: Delay discounting is the tendency when people choose an immediate smaller reward over a delayed, larger reward in decision-making. Higher delay discounting is associated with maladaptive behaviours that can interfere with long-term goal pursuits, whilst low delay discounting is associated with better outcomes in health, academic, and social domains. Episodic Future Thinking is a promising strategy for decreasing delay discounting. Narrative Episodic Future Thinking (NEFT) has shown to be more effective than traditional Episodic Future Thinking. NEFT involves imagining life experiences in personal narratives, therefore imagining future events with a theme makes the events more meaningful, and better able to influence decision-making. This proof-of-concept study aimed to discover if it is feasible to build upon the success of NEFT intervention online and how it may impact on goal salience.Methods: Adults (N = 147) from the general population were recruited from social media, the university’s Participant Registry and in local community areas. Participants (N = 63) were randomly allocated to Episodic Recent Thinking (ERT) or NEFT group and attended an online session where they mentally visualised past events or a series of connected future events over several time-points. They rehearsed the mental imagery using cues generated at their allocated group for two weeks.Results: Repeated measures ANOVAs showed a significant main effect of time and a significant interaction effect between group and time. Participants allocated to NEFT had reduced delay discounting score and increased goal likeliness over time whilst participants allocated to ERT had increased delay discounting score and decreased goal likeliness over time.Conclusion: As 84.13% of participants who participated in intervention completed the study, all participants successfully generated cues online, and online NEFT significantly reduced delay discounting, this study demonstrated that running NEFT intervention online to reduce delay discounting in the general population is feasible.